Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.neuron.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cells Are the Primary Phagocytes in the Fragmentation and Clearance of Degenerating Dendrites in Drosophila

Abstract: SUMMARY During developmental remodeling, neurites destined for pruning often degenerate on-site. Physical injury also induces degeneration of neurites distal to the injury site. Prompt clearance of degenerating neurites is important for maintaining tissue homeostasis and preventing inflammatory responses. Here we show that in both dendrite pruning and dendrite injury of Drosophila sensory neurons, epidermal cells rather than hemocytes are the primary phagocytes in clearing degenerating dendrites. Epidermal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(187 citation statements)
references
References 70 publications
3
182
0
2
Order By: Relevance
“…However, the dendrite pruning defects caused by those UPS mutants are much stronger than the phenotypes caused by caspase inactivation, which mostly causes a delay in the phagocytic uptake of severed dendrites by the epidermis (6,34). Although we cannot exclude that ubcD1 and VCP contribute to caspase activation during pruning, the new mechanism proposed herecontrol of RNA-binding proteins and MICAL expression-likely makes a much stronger contribution to the drastic pruning phenotypes of UPS mutants.…”
Section: Resultsmentioning
confidence: 81%
“…However, the dendrite pruning defects caused by those UPS mutants are much stronger than the phenotypes caused by caspase inactivation, which mostly causes a delay in the phagocytic uptake of severed dendrites by the epidermis (6,34). Although we cannot exclude that ubcD1 and VCP contribute to caspase activation during pruning, the new mechanism proposed herecontrol of RNA-binding proteins and MICAL expression-likely makes a much stronger contribution to the drastic pruning phenotypes of UPS mutants.…”
Section: Resultsmentioning
confidence: 81%
“…[28][29][30][31] Previously, we found that Draper was required earlier in oogenesis for the clearance of nurse cells undergoing apoptosis in response to starvation. 32 Interestingly, we also found that overexpression of Draper in follicle cells was sufficient to kill the underlying germline cells.…”
Section: Role Of Engulfment Genes In Nurse Cell Deathmentioning
confidence: 99%
“…Fly stocks used in this study were as follows: (1) (Han et al, 2014). The lobula Gal4 lines are listed in Table 1.…”
Section: Fly Strainsmentioning
confidence: 99%